Kajian Ancaman Malware dan Upaya Pencegahan melalui Penguatan Keamanan Sistem Komputer - Khaira Ulvi; Garwita Rasikha; Raudatul Aulia; Shella Rika; Maulida Hidayani (JIKUM: Jurnal Ilmu Komputer, 2026)
Malware is one of the most significant threats to computer system security and continues to evolve alongside rapid advances in information technology. The increasing reliance on digital systems in various sectors has made organizations and individuals more vulnerable to malware attacks, which can result in data breaches, system failures, financial losses, and operational disruptions. This study aims to examine the various types of malware threats and to analyze prevention strategies through strengthening computer system security. The research method employed is a systematic literature review by analyzing scientific journal articles, books, and official cybersecurity reports published between 2018 and 2024. The results indicate that malware such as viruses, worms, trojans, ransomware, and spyware exhibit different attack vectors, behaviors, and impacts. Effective prevention measures include the implementation of updated antivirus software, firewalls, regular system and application updates, data backup mechanisms, user awareness training, and the enforcement of organizational security policies. A comprehensive approach to strengthening computer system security is essential to reducing malware risks and enhancing overall information security resilience.